EFFECT OF BLOOD GLUCOSE CONTROL TOWARDS PLASMA AND VITREOUS LEVELS OF VASCULAR ENDOTHELIAL GROWTH FACTOR AND PLACENTAL GROWTH FACTOR IN DIABETIC RATS - Anggun Rama Yudantha; Nina Asrini Noor; Joedo Prihartono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Purpose: To compare plasma and vitreous level of vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) in diabetic rats with poor blood glucose (BG) control, reconstitution of good BG control, and nondiabetic rats, and to investigate the effect of reconstitution of good BG control to VEGF and PlGF plasma and vitreous level. Methods: This is an experimental study using eighteen Sprague Dawley rats which were divided into intervention group (n=14) and control group (n=4). Intervention group were given Streptozotocin (STZ) injection to induce diabetes. After 4 weeks, intervention group was randomly divided into group I for termination and group II for reconstitution of good BG control with insulin for the following 4 weeks, and so was the control group. Plasma and vitreous samples were taken. VEGF and PlGF levels were evaluated with enzyme-linked immunosorbent assay (ELISA). Results: Seventeen of 18 rats survived in intervention group. BG level of intervention group II decreased dramatically to normoglycemia. ELISA at month 1 showed that VEGF vitreous level tend to be higher in intervention group I compared to control I, 196.36 ± 65.24 pg/dL and 123.64 ± 44.99, respectively (p=0.20). ELISA at month 2 showed that PlGF vitreous level of intervention group I were significantly higher compared to control I, 59.04 ± 2.48 and 51.93 ± 3.15, respectively (p=0.01). Vitreous and plasma VEGF of intervention group I and II were not different, while vitreous and plasma PlGF were significantly higher in group II. Conclusions: Vitreous levels of VEGF and PlGF were increased in diabetic rats compared to nondiabetic, and reconstitution of good BG control for 1 month were unable to reduce VEGF and PlGF levels.